dl-Asparaginium perchlorate - Guenifa, Fatiha (International Union of Crystallography, 2009)
Two enantiomeric counterparts (l- and d-asparginium cations related by glide planes) are present in the structure of the title compound, C(4)H(9)N(2)O(3) (+)·ClO(4) (−), with a 1:1 cation–anion ratio. The structure is built up from asparginium cations and perchlorate anions. In the crystal, molecules assemble in double layers parallel to (100) through N—H⋯O, O—H⋯O and C—H⋯O hydrogen bonds. In the asparginium layers, hydrogen bonds generate alternating R (2) (2)(8) and R (4) (3)(18) graph-set motifs. Further hydrogen bonds involving the anions and cations result in the formation of a three-dimensional network.